Characterization of Surface Films Formed on Aluminum during Mass-Transfer Limited Anodic Dissolution in Phosphoric Acid. Issue 2 (23rd December 2016) - Baldhoff, T.; Marshall, A. T.
Abstract : Electrochemical impedance spectra recorded during the mass-transfer limited dissolution of commercially pure aluminum rotating disk electrodes in concentrated phosphoric acid are presented. The influence of rotation rate and potential on the observed capacitive and inductive semi-circles is discussed and the presence of a salt film on top of the oxide film is debated. The impedance spectra are interpreted hypothesizing the presence of a compact, barrier-type Al2 O3 film only. The capacitive and inductive features are explained in terms of the capacitive charging of the barrier film, the relaxation of a surface charge at the film/solution interface and the perturbation of the film thickness. The properties of the film such as electric field strength, half-jump distance and polarizability of the film/solution interface are calculated in agreement with literature values.